Thank you, teachers, for your selfless contributions to nation - Abd Razak, Dzulkifli (2004)
Today is Hari Guru, or Teachers' Day, the day we pay tribute to those men and women who have in no small way made us what we are. It is a time to remind ourselves of their selfless contributions to the nation since preMerdeka days. Hari Guru is, therefore, an important day not only to record our appreciation of all those in the teaching profession but also, more urgently, to assist in raising it to the level that it deserves. Of late, there are so many in other professions "stealing" the limelight and attention from teachers.